Converting Malfunctioned Fully Automatic (Electro-Mechanical Driven) to Semiautomatic Washing Machine - Bajet, Jr., Manuel A.; Bajet, Nelson A.; Tolentino, Oswald T. (JPAIR Multidisciplinary Research, 2013)
This study converted a damaged fully automatic washing machine into a semi -automatic washing machine. Conversion of the machine was done due to unavailability of its electronic spare parts in the local market and to recycle the equipment. Thus, the study explored the conversion the washing machine that can be shared to the local technician to enhance their knowledge, skills and minimize environmental waste. It involved dismantling and rewiring, identifying the terminal leads of the motors, and testing recycled parts. Replacement of unserviceable part was done to turn into operation the said machine. Findings disclosed that the automatic washing machine converted into a semi-automatic have the similar operation cycles. The only difference between the two washing machines was the controls and sequence of washing. In semiautomatic washing machine, it requires human intervention to control and to add and drain water. Cost incurred in converting the malfunction automatic washing machine into a semi-automatic function was much cheaper than buying a brand new one.
Keywords: Discarded Electronics; Washing Machine; Semi-Automatic; Vigan City; Ilocos Sur; Philippines